Penentuan Kualitas Palm Kernel Layak Produksi Menggunakan Metode Weighted Product dan Weighted Aggregated Sum Product Assesment - Siagian, Indriana; Samsudin, Samsudin (Program Studi Teknik Informatika Universitas Pamulang, 2024)
PT Okta Palm Oil stands 2018 managing the earth's produce i.e. palm kernel or known as palm kernel. In the palm kernel oil industry or often referred to as palm kernel oil, quality is a very important factor for continuity in business. However, the production of palm kernel oil has always received rejection from some related companies due to the large number of qualities that do not meet the standards because the system in use is still in place. For that reason the availability of this research could help in the decision-making of palm kernels that have been eligible for further production. The aim of this research is to create decision support applications using PHP, MYSQL, XAMPP and using research and development methods i.e. potentials and problems, data collection to application testing. Testing of the system is carried out by experts, testers and by users. In order to determine the quality rate of palm kernels that have gone through the purification process, it should correspond to the standard established by the enterprise with the provision as follows: acid rate (max 5%), water rate (max 8%), dirt rate (max 8%), debris by 35%, and oil content of 51%. From the results of the research it is known that to determine the quality of the palm kernel it takes a very long process for which the availability of supporting applications this decision is considered very helpful, the result obtained is very valid where out of the 31 samples taken there are 14 that are not worthy of production and as many as 17 that are qualified for production.